2007
DOI: 10.1562/0031-8655(2001)0730669mtrdpt2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Tumor Response During Photodynamic Therapy Using Near-infrared Photon-migration Spectroscopy¶

Abstract: Benzoporphyrin-derivative (BPD)-monoacid-ring A photodynamic therapy (PDT) was performed on subcutaneous tumor implants in a rat ovarian cancer model. In order to assess PDT efficacy the tumor and normal tissue optical properties were measured noninvasively prior to and during PDT using frequency-domain photon migration (FDPM). FDPM data were used to quantify tissue absorption and reduced scattering properties (given by the parameters a and s , respectively) at four nearinfrared (NIR) wavelengths (674, 811, 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is desirable to do concurrent, real-time measurements during PDT and a while after PDT. Previous studies showed that real-time measurements during PDT can provide predictive information [5,18,35,38,41,43,50,51]. It is possible to “filter-out” the treatment light during non-invasive measurements to extract noninvasive parameters during PDT.…”
Section: Resultsmentioning
confidence: 99%
“…It is desirable to do concurrent, real-time measurements during PDT and a while after PDT. Previous studies showed that real-time measurements during PDT can provide predictive information [5,18,35,38,41,43,50,51]. It is possible to “filter-out” the treatment light during non-invasive measurements to extract noninvasive parameters during PDT.…”
Section: Resultsmentioning
confidence: 99%
“…In subcutaneous rat tumors the PDT-induced difference in tumor SO 2 was correlated with histological damage (area of necrosis) at 3 days after PDT [24]. Also, luminescence-based monitoring of singlet oxygen production in mouse skin during PDT demonstrates a strong correlation between cumulative singlet oxygen count and response to treatment [27].…”
Section: Therapeutic Consequences Of Pdt-created Hypoxiamentioning
confidence: 86%
“…Recently, optical technology has been applied toward the goal of noninvasively monitoring tumor oxygenation in PDTtreated animals [12,[24][25][26]. In studies by Wang et al, diffuse reflectance spectroscopy (DRS) was used to measure tumor hemoglobin oxygen saturation (SO 2 or S t O 2 ) immediately before and after Photofrin-PDT (5 mg/kg, 38 mW/ cm 2 , 135 J/cm 2 ).…”
Section: Therapeutic Consequences Of Pdt-created Hypoxiamentioning
confidence: 99%
“…Indeed, Woodhams, et al [118] reported low fluence rate to lead to a slower rate of decline in the oxygen saturation of liver tissue during the course of light delivery for PDT mediated by aluminum disulphonated phthalocyanine. The power for hemodynamic monitoring to predict PDT-created cytotoxicity or treatment outcome has been demonstrated in rodent studies by several groups [119][120][121][122], including investigations that employed instruments based in DRS or DCS [119,121,122]. More recently, DCS has also been used to identify differences in the consistency of blood flow cycles in murine tumors that may be indicative of the sensitivity of the blood vessels to subsequent stresses such as PDT ( Fig.…”
Section: Techniques For Measuring Oxygenation and Blood Flowmentioning
confidence: 99%